Development of spray dried sugar cane powder - Khomathan, Valayetham (2009)
This study explains the process and the best parameters to dry sugarcane juice using laboratory scale spray dryer. The raw sugarcane juice bought is filtered in the lab before the process of spray drying. In this process various amount of maltodextrin is added to identify the best amount of maltodextrin that should be added in sugarcane juice. Once the component of maltodextrin is determined, the variation in the temperature is done to find out the optimum temperature. For the part of analytical experiment, solubility test is done using the lab scale centrifugal machine. Solubility test is done on the various amount of matodextrin. Calcium carbonate is used as the anti-caking agent to study the caking ability of the produced powder. Sugarcane powder with the best conditions are done with anti-caking agent and stored in shelf for one month. The final test done is the sensory evaluation. In this evaluation students were randomly picked in the cafeteria. They were given the reconstituted juice and the produced powder to evaluate. The criteria being evaluated in this part are the appearance, flavor and the texture. The students were asked to rank all this categories following the scale of 1 to 5. From this evaluation the commercial value of produced sugarcane can be studied. From this research, it was found that sugarcane juice can be powderised using the lab scale spray dryer. The suitable amount of maltodextrin 20% and the optimum temperature is at 170°C. Sugarcane juice with higher amount of maltodextrin has the highest solubility. Powder with the anti-caking agent can be stored longer then the powder produced without anti-caking agent. This sugarcane powder has commercial values and can be marketed.